What are my students doing? Introducing ELENA, the E-Learning Event Notification Architecture - Caeiro, Manuel; Fontenla, Jorge; Llamas, Martin (Cadernos de Informática, 2011)
In this article we introduce ELENA, a new architecture for notifying events to a Learning Management System (LMS) by an external tool. At the core of this work is the idea of integrating external tools exposed as Web Services. Although some progress is being done in this field by the research community, current solutions achieve at best a very ``soft’’ integration, it is, the LMS can link an external tool but cannot monitor or alter its workflow. The ELENA system tries to alleviate this problem by introducing an architecture that allows an LMS to track the use that teachers and students make of the tool. Therefore, the LMS can have a greater control over the integrated tools. The ELENA system is based on Web Services and specific APIs and protocols, resulting on a simple and scalable architecture.